2021
DOI: 10.1002/jia2.25842
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and initiation of antiretroviral treatment at enrolment into HIV care in Cameroon under a national “treat all” policy: a cross‐sectional analysis

Abstract: IntroductionRapid antiretroviral treatment (ART) initiation reduces time from HIV infection to viral suppression, decreasing HIV transmission risk. Mental health symptoms may influence timing of ART initiation. This study estimated the prevalence of ART initiation at enrolment into HIV care and the relationship between mental health and ART initiation at enrolment into HIV care.MethodsWe conducted interviews with 426 individuals initiating HIV care in Cameroon between June 2019 and March 2020 to estimate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Importantly, we have also found more than twice the risk of death in index participants with moderate or severe depression. The causal pathway of this association is described by multiple studies showing the negative impact of depression at each stage of HIV treatment continuum: care engagement [ 28 ], ART initiation and adherence [ 29 31 ], and viral suppression [ 32 , 33 ], resulting in higher mortality [ 34 36 ]. However, some studies reported an independent effect of depression on mortality, controlling for the effects of adherence [ 37 , 38 ] and clinical variables [ 35 , 39 ], potentially suggesting other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have also found more than twice the risk of death in index participants with moderate or severe depression. The causal pathway of this association is described by multiple studies showing the negative impact of depression at each stage of HIV treatment continuum: care engagement [ 28 ], ART initiation and adherence [ 29 31 ], and viral suppression [ 32 , 33 ], resulting in higher mortality [ 34 36 ]. However, some studies reported an independent effect of depression on mortality, controlling for the effects of adherence [ 37 , 38 ] and clinical variables [ 35 , 39 ], potentially suggesting other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests the high prevalence of mental disorders among PWH may be influenced by HIV-related stigma and worry about the impact one’s HIV status has on interpersonal relationships and economic stability [ 6 ]. Mental disorders have been associated with poor HIV treatment outcomes, including delayed HIV treatment initiation, suboptimal adherence to ART, and poor retention in care [ 1 , 3 , 7 11 ]. Despite the high prevalence of mental disorders among PWH and the relationship with suboptimal HIV treatment outcomes, integration of mental health care into HIV care remains limited throughout SSA [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…HIV prevalence among adults ages 15–49 in Cameroon is 2.9% [ 21 ], though prevalence varies by region [ 22 ]. Among PWH initiating HIV care in Cameroon, moderate to severe symptoms of depression, anxiety, and PTSD were reported by 20%, 12%, and 15% of PWH, respectively [ 10 , 11 ]. Cameroon’s scarcity of mental health professionals and limited resources highlights the pressing need to identify feasible strategies to address mental health needs in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial stressors have been associated with increased prevalence of mental and substance use disorders among PWH [7,12,13]. Psychosocial stressors and mental and substance use disorders have been consistently associated with poor HIV treatment outcomes, including engagement into HIV care with advanced HIV, delayed ART initiation, poor ART adherence, and virologic failure [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%